Modulating the magnetization dynamics of four phenoxo-O bridged Dy2 complexes based on a Schiff base derived from 8-hydroxyquinoline. (20th September 2018) - Wu, Dong-Fang; Shen, Hai-Yun; Chu, Xiao-Ya; Chang, Wen-Ju; Zhao, Li-Hua; Duan, Yao-Yao; Chen, Huan-Huan; Cui, Jian-Zhong; Gao, Hong-Ling
Abstract : The quantum tunneling process in Dy-SMMs is suppressed by the application of a dc field. Abstract : Four novel μ-O bridged dinuclear Dy2 clusters have been synthesized successfully by utilizing an 8-hydroxyquinoline (8-HQ) Schiff base ligand and four different co-ligands: [Dy2 (bfa)2 (L)2 (H2 O)2 ]·4CH3 OH (1 ), [Dy2 (TTA)2 (L)2 (H2 O)2 ]·4CH3 OH (2 ), [Dy2 (acac)2 (L)2 (H2 O)2 ]·2H2 O (3 ) and [Dy2 (PhCOO)2 (L)2 (H2 O)2 ] (4 ) (Hbfa = benzoyl trifluoroacetylacetone, HTTA = thiophene trifluoroacetylacetone, Hacac = acetylacetone, PhCOOH = benzoic acid, H2 L = 2-[(4-pyridinebenzoylhydrazone)methyl]-8-hydroxyquinoline). Magnetic studies show that only complex1 exhibits SMM behavior under a zero dc field with a magnetic relaxation barrier of 68.89 K. When a dc field of 1500 Oe is applied, the value of Δ E / k B increases to 72.63 K. The different dynamic magnetic behaviors of the four Dy2 complexes mainly originate from the tiny changes of the coordination environment and magnetic coupling interaction of the central ions caused by the different co-ligands. Meanwhile, it proves that the co-ligands play an important role in modulating the magnetic properties of Dy-SMMs based on 8-HQ derivatives.